Examining How Treatment Fidelity Is Supported, Measured, and Reported in K–3 Reading Intervention Research - Capin, Philip (Educ Psychol Rev, 2017)
Treatment fidelity data (descriptive and statistical) are critical to interpreting and generalizing outcomes of intervention research. Despite recommendations for treatment fidelity reporting from funding agencies and researchers, past syntheses have found treatment fidelity is frequently unreported (e.g., Swanson, The Journal of Special Education, 47, 3–13, 2011) in educational interventions and fidelity data are seldom used to analyze its relation to student outcomes (O’Donnell, Review of Educational Research, 78(1), 33–84, 2008). The purpose of this synthesis was to examine how treatment fidelity is supported, measured, and reported in reading intervention studies conducted with students at risk or with reading difficulties in grades K–3 from 1995 through 2015. All studies (k = 175) were coded to extract and classify information related to (a) the characteristics of the intervention study (e.g., publication year, research design); (b) treatment implementer training and support; (c) treatment fidelity data collection procedures, dimensions (i.e., adherence, quality, receipt, dosage, and differentiation), and levels of treatment fidelity data; and (d) the use of fidelity scores in the analysis of treatment effects. Results indicated that less than half (47%) of the reading intervention studies synthesized reported treatment fidelity data (numeric or narrative). Exploratory analyses showed that several study features were associated with the prevalence of fidelity reporting. Studies reporting treatment fidelity largely measured treatment adherence, and scores were, on average, high. Other dimensions of treatment fidelity (e.g., treatment differentiation), and analyses relating fidelity data to outcomes, were consistently absent from the corpus of reading intervention studies reviewed. Recommendations for enhancing how treatment fidelity data in intervention studies are collected and reported are presented.